A study of clinical, etiological and neurodevelopmental profile of epilepsy in children aged 0-5 years - Chanpura, Vaishali R.; Mori, Hardev T. (International Journal of Contemporary Pediatrics, 2021)
Background: Seizures constitute the most common neurological problem in children. Appropriate diagnosis and management of childhood epilepsy is essential to improve quality of life in them. Objectives of the study were to study the clinical and etiological profile of early childhood epilepsy and its effect on neurodevelopment. Methods: This was a time bound study; duration being one year from September, 2018 to September 2019. All new patients with acute seizures or status epilepticus admitted in paediatric emergency ward were evaluated and those meeting inclusion criteria were enrolled. On the basis of history, neurological and systemic examination and available investigations primary diagnosis of epilepsy was reached. Neurodevelopmental parameters like vision, hearing, and DQ were assessed. EEG was done in all patients. Other relevant investigations like neuroimaging were carried out when indicated. Collected data was analysed in form of frequency and percentage. Results: A total of 52 patients were enrolled. 60% patients were younger than 2 years. Maximum patients had generalised convulsions; generalised tonic-clonic being the most prevalent. 38% patients had significant perinatal complications like perinatal asphyxia, pyogenic meningitis and kernicterus. Fifty per cent patients had delayed milestones and half of those had severe delay. 67% had abnormal EEG and 20 patients had abnormal neuro-imaging findings. The most common etiologies for epilepsy were hypoxic ischaemic encephalopathy, idiopathic, epilepsy syndromes, metabolic disorders and CNS infections. Conclusions: Majority of early childhood epilepsy is a result of either genetic conditions or perinatal events. They have neurodevelopmental and behavioural associations. While treating epilepsy all these factors should be considered in order to ensure a near-normal life for these patients.